Management Of Purple Blotch Of Onion Caused By Alternaria Porri (Journal of Plant Disease Sciences, 2021)
The purple blotch caused by Alternaria porri is a major onion disease. Certain chemical fungicides were tested in vivo to determine their efficacy against purple blotch. In the field experiment, treatment with bulb dip (Copper oxychloride @ 0.25% + streptomycin @ 200 ppm) + spraying with (Mancozeb @ 0.25% + carbendazim @ 0.1% + copper oxychloride @ 0.25%) treatment recorded lowest per cent disease intensity i.e. 15 % and it showed highest percent disease control i.e. 55.13 %. Maximum seed yield obtained in treatment with bulb dip (Copper oxychloride @ 0.25% + streptomycin 200 ppm) + spraying with (Mancozeb @ 0.25% + carbendazim @ 0.1% + copper oxychloride @ 0.25%) i.e. 1022 kg/ha.
Keywords: Alternaria porri; Purple blotch; Management; Onion